Hourly load shifting approach for demand side management in smart grid using grasshopper optimisation algorithm. Issue 5 (3rd February 2020) - Jamil, Majid; Mittal, Sonam
Abstract : In this new era of communication, the advent of the smart grid has revolutionised the power system network. The goal of smart grids is to provide a more reliable, environment‐friendly and economically efficient power system. Demand side management or demand side response is one of the key components of the smart grid which accomplishes the smart grid that would provide intelligence to the traditional grid. Here, a new approach has been proposed for the demand side management, which is based on shifting a load from peak to off‐peak time. The main objective of the work is to reduce the peak hour demand and the utility bill of the consumers. To achieve these objectives, the proposed strategy is modelled as a minimised optimisation problem and it tries to find out the optimal solution. For that, two optimisation algorithms, the first one is particle swarm optimisation algorithm and the second one is grasshopper optimisation algorithm, are proposed and applied in three area loads of the smart grid, i.e. residential, commercial and industrial. The obtained simulation results show a significant reduction in peak hour demand and utility bills.